(untitled) (Veterinary Science, 2022)
Accidents caused by Loxosceles spiders are important in Veterinary Medicine due to the severity of the injury they cause and the possible systemic complications that can lead to the animal’s death. However, there are few epidemiological records. This is why it is necessary to generate basic knowledge to consider loxoscelism as a possible condition, to generate an early diagnosis from clinical data and anamnesis, with the identification of the animal that caused the accident when it is possible. The present study aims to describe the evolution of the lesions probably caused by Loxosceles sp. poisoning in a 6-year-old female canine, 7 kg, Fox Terrier breed, received at the Small Animal School Hospital of Veterinary Sciences Faculty, UNLPam. Lesions were observed on the left ocular conjunctiva, with evident bleeding, left upper lip with swelling and hematoma also with bleeding; edema and bruising of hind limbs in the popliteal and thigh regions. Laboratory studies showed hemolytic anemia and coagulopathy signs. The animal was treated with specific antivenom, fresh whole blood transfusion, corticosteroids, and antibiotics. Based on the clinical data and the evidence of the presence of Loxosceles sp. in the house (ootheca and molts), it is conjectured that this could be a case of dermo-hemolytic loxoscelism, with favorable evolution of the patient one week later, despite the severity of the case.